THE EFFECT OF USING MIND MAPPING TECHNIQUE ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 40 PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Nova Situmorang; Rumiri Rumiri; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study is to find out whether or not there was a significant effect of using mind mapping technique on the ability of the second year students of SMPN 40 Pekanbaru in writing descriptive text. This research was conducted at SMPN 40 Pekanbaru which is located on Jl. Garuda Sakti Kec. Tampan Pekanbaru and had been started from August, 2017 till September, 2017. The population in this research was the second year students of SMPN 40 Pekanbaru. The number of entire population was 170. The researcher used cluster random sampling technique to determine the sample. The participant of this research was 43 students of VIII.A class. This research focuses on the students’ writing ability in writing descriptive texts before and after the treatment that can be seen from their score on the given writing tests. The result proved that mind mapping is effective to improve the students’ writing ability especially in writing descriptive texts. It can be seen from the students’ mean score on post-test (67.32) that was higher than on pre-test (55.73). So, it helped the students to generate their ideas, expand their creativity and understanding of key vocabulary and concepts in simple definitions and integrate their background knowledge into definition. Further, it was suggested that the students may use mind mapping and keep writing in order to accustom themselves to organize and connect the information when they are writing a text. This research can be also used as a reference to conduct further studies related to writing ability.Keywords : Pre-Experiment Research, Writing Ability, Mind mapping, Descriptive Text.